A CACNA1A variant associated with trigeminal neuralgia alters the gating of Cav2.1 channels - Gambeta, Eder (Mol Brain, 2021)
A novel missense mutation in the CACNA1A gene that encodes the pore forming α(1) subunit of the Ca(V)2.1 voltage-gated calcium channel was identified in a patient with trigeminal neuralgia. This mutation leads to a substitution of proline 2455 by histidine (P2455H) in the distal C-terminus region of the channel. Due to the well characterized role of this channel in neurotransmitter release, our aim was to characterize the biophysical properties of the P2455H variant in heterologously expressed Ca(V)2.1 channels. Whole-cell patch clamp recordings of wild type and mutant Ca(V)2.1 channels expressed in tsA-201 cells reveal that the mutation mediates a depolarizing shift in the voltage-dependence of activation and inactivation. Moreover, the P2455H mutant strongly reduced calcium-dependent inactivation of the channel that is consistent with an overall gain of function. Hence, the P2455H Ca(V)2.1 missense mutation alters the gating properties of the channel, suggesting that associated changes in Ca(V)2.1-dependent synaptic communication in the trigeminal system may contribute to the development of trigeminal neuralgia.